HUBUNGAN FAKTOR LINGKUNGAN DENGAN KEJADIAN PENYAKIT ISPA PADA MASYARAKAT DESA NANIA KOTA AMBON TAHUN 2020 - Epi Dusra (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2021)
ARI is an acute infection that attacks the respiratory tract, namely the organs that start from the nose to the alveoli along with the adnexa. In general, the risk factors for ARI are physical environmental factors, host factors, agent factors and social environmental factors, physical environmental factors, namely indoor air pollution. , the physical condition of the house. The purpose of this research is to find out how the correlation of knowledge and the environment with the incidence of ARI in the community in Nania Village, Ambon City. The research design used in this research is descriptive analytic research with a cross sectional approach. This research was carried out in Nania Village, Ambon City in July-August 2020. The research sample used was 60 people. The sampling method in this study was simple random sampling. From the research results, it was found that there was a relationship between the incidence of ARI and room occupancy density, a value of 0.000 was obtained, there was a relationship with the type of floor, a value of 0.000 was obtained, there was a relationship with the type of wall, a value of 0.000 was obtained, there was a relationship with the ceiling of the house, a value of 0.000 was obtained, there is a lighting relationship obtained a value of 0.000. So it can be concluded that there is a significant relationship with the incidence of ARI in the Nania village community, Ambon city.